Entropy at Bio–Nano Interfaces - Zhu, Guolong; Xu, Ziyang; Yan, Li-Tang (Nano letters, 2020)
Entropy, one of the central concepts of thermodynamics, can be a predominant contribution to structural formation and transition. Although it is well-known that diverse forces and energies can significantly contribute to the structures and activities at bio–nano interfaces, the potential entropic contribution remains less well understood. Therefore, this review article seeks to provide a conceptual framework demonstrating that entropy can be exploited to shape the physicochemical properties of bio–nano interfaces and thereby regulate the structures, responses, and functions of biological systems. We introduce the typical types of entropy that matter at bio–nano interfaces. Moreover, some key characteristics featuring entropy at bio–nano interfaces, such as the difference between entropic force and energetic interaction and the associated implications for biomimetic research, are discussed. We expect that this review could stimulate further effort in the fundamental research of entropy in biology and in the biological applications of entropic effects in designer biomaterials.